2005
DOI: 10.1017/s0012162205000964
|View full text |Cite
|
Sign up to set email alerts
|

Seminars in the Psychiatry of Learning Disabilities (2nd edn), Edited by William Fraser and Michael Kerr, London: Gaskell, 2003, pp 320, £20.00, ISBN 1 901242 93 5 (Paperback)

Abstract: 2002) Risperidone in children with autism and serious behavioural problems. N Engl J Med 347: 314-321. 35. Barnard L, Young AH, Pearson J, Geddes JJ, O'Brien G. (2002) A systematic review of the use of atypical antipsychotics in autism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Lifestyle factors including high obesity rates (Glover et al, 2017) and unhealthy lifestyle choices also contribute. People, with poor access to lifestyle advice are less equipped to make informed decisions on healthy living, smoking and alcohol intake (Baxter et al, 2003;Winter, 2014).…”
Section: Cardiovascular Health and Associated Conditionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Lifestyle factors including high obesity rates (Glover et al, 2017) and unhealthy lifestyle choices also contribute. People, with poor access to lifestyle advice are less equipped to make informed decisions on healthy living, smoking and alcohol intake (Baxter et al, 2003;Winter, 2014).…”
Section: Cardiovascular Health and Associated Conditionsmentioning
confidence: 99%
“…Closely linked to the increased cardiovascular disease risk, is the high prevalence of obesity, metabolic syndrome and diabetes (Baxter et al, 2003;Winter, 2014) Obesity has been suggested to affect between 19.1 and 27.5% of men and between 27.5 and 58.5% of women with intellectual disability (Baxter et al, 2003). The main contributor to obesity, diabetes and metabolic syndrome is sedentary lifestyle (Baxter et al, 2003;Winter, 2014).…”
Section: Cardiovascular Health and Associated Conditionsmentioning
confidence: 99%
See 3 more Smart Citations